Tracing the Evolution of Carbon Tax Research: A Bibliometric Analysis of Global Publication Trends - Siti Maghfiroh; Aprilia Nastiti Rahayu (Jurnal Akuntansi dan Bisnis, 2025)
Greenhouse gas (GHG) emissions have increased in all sectors since 2010. A carbon tax is one of the policies that tackle carbon emissions. Research on the carbon tax is growing along with climate change mitigation commitments. This study aims to identify the historical development of carbon tax literature and map future research directions using bibliometric methods. This research tries to answer questions related to the trends and historical development of carbon tax literature from 2010-2024. This research uses the Scopus and NVivo databases as additional tools to justify the articles used. This research applied the PRISMA protocol and bibliometric analysis approach. The Scopus database was explored to analyze trends, co-occurrence, co-authorship, co-citation, citation analysis of 2,406 articles, with publication years 2010-2024. The keyword "carbon tax" was the most frequently occurring keyword, with a total of 193 occurrences. In terms of collaboration, Edenhofer, Ottmar is the highest collaborating author. The United States had the highest international collaboration with a total of 211 documents and 30 relationships. Publications by Stern, (2008), Acemoglu et al., (2012), and Golosov et al., (2014) were frequently cited together. Articles by Aghion et al. (2016) and Energy Economics were the most cited documents and journals in carbon tax research. Overall carbon tax research has increased. Future research could explore the phenomenon of disparity between countries that have implemented carbon tax policies and countries that are widely researched in this topic, as well as sub-topics that remain under-researched.